Climate change in Colorado: executive summary - Bolinger, Rebecca, author; Lukas, Jeff, author; Schumacher, Russ, author; Goble, Peter, author; Colorado Climate Center, publisher (Colorado State University. Libraries, 2024)
Executive summary of the third edition of the Climate Change in Colorado Report which describes recent trends and future projections of Colorado's climate and hydrology.
Keywords: Colorado -- Climate -- Observations; Climatic changes -- Colorado; Meteorology -- Colorado -- Observations